The international spirits industry. - Wakely, John (International Trade Ser., 2001)
Although consumption of spirits on a global scale is vast, the spirits industry derives its profits from a relatively small number of countries and product lines. This book provides an overview of all aspects of the industry, covering all the major categories of spirits, and contains a wealth of information on trading statistics, regulations and consumption patterns. It discusses the challenges facing the giant companies, profiling the leading companies in detail, and assesses whether their structure is appropriate to long-term success in the industry. The international spirits industry offers.